2021
DOI: 10.1093/reseval/rvab002
|View full text |Cite
|
Sign up to set email alerts
|

The production of scientific and societal value in research evaluation: a review of societal impact assessment methods

Abstract: Over the past two decades, several methods have been developed to evaluate the societal impact of research. Compared to the practical development of the field, the conceptual development is relatively weak. This review article contributes to the latter by elucidating the theoretical aspects of the dominant methods for evaluating societal impact of research, in particular, their presuppositions about the relationship between scientific and societal value of research. We analyse 10 approaches to the assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 51 publications
0
46
0
4
Order By: Relevance
“…Even if the interest in societal impact was initially conceived as a strategy to assess the returns of government R&D investments (Miettinen et al, 2015), it also covers the societal benefits of research in social, cultural, and environmental dimensions and also sustainability (Bornmann, 2013). Smit and Hessels (2021) of the university. Assessing impact from an economic and quantitative perspective causes such problems as causation and attribution, as it is difficult to detect causeand-effect relationships and attribute certain results to specific actors or interventions (Temple et al, 2018).…”
Section: Sl In the Framework Of Institutional Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if the interest in societal impact was initially conceived as a strategy to assess the returns of government R&D investments (Miettinen et al, 2015), it also covers the societal benefits of research in social, cultural, and environmental dimensions and also sustainability (Bornmann, 2013). Smit and Hessels (2021) of the university. Assessing impact from an economic and quantitative perspective causes such problems as causation and attribution, as it is difficult to detect causeand-effect relationships and attribute certain results to specific actors or interventions (Temple et al, 2018).…”
Section: Sl In the Framework Of Institutional Activitiesmentioning
confidence: 99%
“…On the other hand, Heyeres et al's (2019) review of case studies as impact assessment tools reveals that little attention is usually given to the needs of target populations and to the economic value of research, claiming major transparency in the way in which resources are used. Finally, the 10 assessment methods that Smit and Hessels (2021) gather differ in the very concept of societal value, and especially in the types and roles of supporting actors in knowledge production processes and in the mechanisms of interaction that promote the transfer of knowledge. With its limitations, case studies have the advantage of adjusting to the great diversity of scenarios and social actors that can intervene in generating impact, even in the same field of knowledge (Janker & Mann, 2018).…”
Section: Sl In the Framework Of Institutional Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is through the intertwined processes of knowledge production, translation, communication, and utilization that efforts to 'valorise' research by and for different research users occurs. Similar to Smit and Hessels (Smit & Hessels, 2021), our conceptualisation of value from research is open, inclusive, and does not grant a priori ascendency to science or society. Based on this understanding, the paper conducts an exploratory empirical study of interconnections among research-related knowledge processes.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches are useful for reconstructing pathways between research activities, research outputs, and linked outcomes at the level of specific research projects, programmes, or organisations (Matt et al, 2017). Each of these approaches treats the conceptualisation of societal value from research differently (Smit & Hessels, 2021) and focuses on different configurations of connections between 'science and non-science' entities (Costas et al, 2021). This paper seeks to contribute to this discussion and to empirical analysis of the generation of value from research in society, but in a different way to that found in the 'research impact' literature.…”
Section: Introductionmentioning
confidence: 99%